Dementia-related agitation: a 6-year nationwide characterization and analysis of hospitalization outcomes. (1st February 2023) - Ferreira, Ana Rita; Gonçalves-Pinho, Manuel; Simões, Mário R.; Freitas, Alberto; Fernandes, Lia
Abstract: Objectives: To characterize all hospitalizations held in mainland Portugal (2010–2015) with dementia-related agitation based on International Classification of Diseases, Ninth Revision, Clinical Modification (ICD-9-CM) coding, and to investigate whether there is a relationship between agitation and hospitalization outcomes. Methods: A retrospective observational study was conducted using an administrative dataset containing data from all mainland Portuguese public hospitals. Only hospitalization episodes for patients aged over 65 years who have received a dementia diagnosis ascertained by an ICD-9-CM code of dementia with behavioral disturbance (294.11 and 294.21) and dementia without behavioral disturbance (294.10 and 294.20) were selected. Episodes were further grouped according to the presence of an agitation code. For each episode, demographic data and hospitalization outcomes, including length of stay (LoS), in-hospital mortality, discharge destination and all-cause hospital readmissions, were sourced from the dataset. Comparative analyses were performed and multivariable logistic methods were used to estimate the adjusted associations between agitation (exposure) and outcomes. Results: Overall, 53, 156 episodes were selected, of which 6, 586 had an agitation code. These were mostly related to male, younger inpatients (mean 81.19 vs. 83.29 years, p <  0.001), had a higher comorbidity burden, stayed longer at the hospital (median 9.00 vs. 8.00 days, p <  0.001) and frequently ended being transferred to another facility with inpatient care. Agitation was shown to independently increase LoS (aOR = 1.385; 95%CI:1.314–1.461), but not the risk of a fatal outcome (aOR = 0.648; 95%CI:0.600–0.700). Conclusion: These results support the importance of detecting and managing agitation early on admission, since its prompt management may prevent lengthy disruptive hospitalizations.